Evidence of validity and reliability of the Employability Competencies Measurement Scale (EMCE) in the student population of the National University, Costa Rica (Costa Rican Journal of Guidance & Counseling, 2024)
Objective: Obtain evidence of validity and reliability of the scale for measuring employability skills in students of the third and fourth level of high school in 2022, in accredited courses of the National University.Methodology: It is based on the quantitative paradigm, with a non-experimental design and a descriptive scope. The sample included 335 active students in the II school year of 2022. The design of the EMCE included three phases: a) determination of the profile of employability competencies, b) standardization of employability competencies, and c) instrumentation of the scale. The statistical analysis of validity and reliability was performed using Jamovi software in version 2.4.14.Results: Content validity by expert judgment showed that the EMCE meets the criteria of clarity, coherence, relevance, and sufficiency. The validation of internal structure, with the Bartlett Test (
Keywords: evidence of validity and reliability; measuring instrument; employability skills; college student; higher education